2008
DOI: 10.1007/s11250-007-9126-x
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of bovine tuberculosis in the transhumant and agro-pastoral cattle herds in the border areas of Katakwi and Moroto districts, Uganda

Abstract: A study to determine the prevalence of bovine tuberculosis in the transhumant and agro-pastoral cattle herds in the border areas of Katakwi and Moroto districts in Uganda was carried out from July 2006 to January 2007 using comparative intradermal tuberculin test containing bovine and avian PPDs. A total of 1470 animals, 612 (41.6%) males and 858 (58.4%) females, 883 (60%) young, 555 (37.8%) adult and 32 (2.2%) old animals were included. The study involved a cross-sectional multistage sampling technique with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
45
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 10 publications
19
45
1
2
Order By: Relevance
“…This finding is in agreement with Inangolet et al (2008), who suggested high levels of infectiousness of bovine TB under the common cattle management practices and humid tropical conditions. However, inefficient close contact between diseased and healthy animals in extensive systems, dairy herds and large herds, and possibly a decrease in virulence and transmission capacity of the causal strains due to adverse weather (Oloya et al 2006), and low infectiousness of the local zebu cattle (Ameni et al 2006(Ameni et al , 2007Inangolet et al 2008), were also characteristics in the study environments. A better resistance or adapted tolerance to bovine TB infection of some local breeds have been suggested (O'Reilly and Daborn 1995;Ameni et al 2008), and could have been the reasons for the lower prevalence rates recorded among the Namchi, Guadali and White Fulani compared to the Red Mbororo cattle.…”
Section: Prevalence Of Bovine Tuberculosis Based On Tuberculin Skin Tsupporting
confidence: 93%
See 4 more Smart Citations
“…This finding is in agreement with Inangolet et al (2008), who suggested high levels of infectiousness of bovine TB under the common cattle management practices and humid tropical conditions. However, inefficient close contact between diseased and healthy animals in extensive systems, dairy herds and large herds, and possibly a decrease in virulence and transmission capacity of the causal strains due to adverse weather (Oloya et al 2006), and low infectiousness of the local zebu cattle (Ameni et al 2006(Ameni et al , 2007Inangolet et al 2008), were also characteristics in the study environments. A better resistance or adapted tolerance to bovine TB infection of some local breeds have been suggested (O'Reilly and Daborn 1995;Ameni et al 2008), and could have been the reasons for the lower prevalence rates recorded among the Namchi, Guadali and White Fulani compared to the Red Mbororo cattle.…”
Section: Prevalence Of Bovine Tuberculosis Based On Tuberculin Skin Tsupporting
confidence: 93%
“…In this study, animal environments were generally humid or wet and favourable for long survival of TB agents (Goodchild and CliftonHadley 2001;Philips et al 2003). However, contradictory results of lower bovine TB prevalence in cattle maintained in traditional pastoral systems in Uganda and Ethiopia were associated with the relatively dryer conditions of the environments (Oloya et al 2006;Ameni et al 2007;Inangolet et al 2008). Traditional pastoral systems in the tropics that create risks characteristic of intensive farming in relation to the transmission of bovine TB have been well documented (O'Reilly and Daborn 1995;Omer et al 2001;Ayele et al 2004).…”
Section: Prevalence Of Bovine Tuberculosis Based On Tuberculin Skin Tmentioning
confidence: 80%
See 3 more Smart Citations